2018
DOI: 10.1002/jcb.27096
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐28‐5p relieves neuropathic pain by targeting Zeb1 in CCI rat models

Abstract: MicroRNAs (miRNAs) are recognized as significant regulators of neuropathic pain. Moreover, neuroinflammation can contribute a lot to the progression of neuropathic pain. MiR-28-5p has been reported to be involved in many pathological diseases. However, little is known about the function of miR-28-5p in neuropathic pain development. Our current study was designed to investigate the biological roles of miR-28-5p in neuropathic pain in a rat model established by chronic sciatic nerve injury (CCI). Here, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The secretion of numerous inflammatory cytokines including COX-2, IL-6, and IL-1β promote the neuropathic pain process. 27 Since the role of miR-194 on neuroinflammation in the neuropathic pain process is unknown, we here designed to explore the potential function of miR-194 in neuropathic pain. We first discovered miR-194 was remarkably downregulated in CCI rat abnormally.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of numerous inflammatory cytokines including COX-2, IL-6, and IL-1β promote the neuropathic pain process. 27 Since the role of miR-194 on neuroinflammation in the neuropathic pain process is unknown, we here designed to explore the potential function of miR-194 in neuropathic pain. We first discovered miR-194 was remarkably downregulated in CCI rat abnormally.…”
Section: Discussionmentioning
confidence: 99%
“…miR-28-5p, as one of the numerous miRNAs, has been reported to be involved in inflammatory responses in a variety of diseases. miR-28-5p upregulation inhibits inflammatory factor expression in rats with chronic sciatic nerve injury 8 and is associated with axial spondylolisthesis. 9 Additionally, miR-28-5p was significantly downregulated in lipopolysaccharide (LPS)-induced myocardial inflammation in rats.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate gene expression by binding to the 3′UTRs of their target mRNAs, and a single miRNA can regulate the expression of multiple genes. Studies have demonstrated that LPP ( 7 ), RAP1B ( 9 ), NRF2 ( 22 ) and ZEB1 ( 23 ) are direct target genes of miR-28-5p. The present study revealed that RAP1B was downregulated by miR-28-5p, which was consistent with the findings of a previous study ( 9 ).…”
Section: Discussionmentioning
confidence: 99%